Accuracy of Periapical Radiography and CBCT in Endodontic Evaluation - R. Lo Giudice; F. Nicita; F. Puleio; A. Alibrandi; G. Cervino; A. S. Lizio; G. Pantaleo (Hindawi Limited, 2018)
Introduction. A radiological evaluation is essential in endodontics, for diagnostic purposes, planning and execution of the treatment, and evaluation of the success of therapy. The periapical radiography is nowadays the main radiographic investigations used but presents some limits as 3D anatomic alteration, geometric compression, and possible anatomical structures overlapping that can obscure the area of interest. CBCT (cone beam computed tomography) in endodontics allows a detailed assessment of the teeth and surrounding alveolar anatomy for endodontic diagnosis, treatment planning, and follow-up. Objective. The purpose of this study was to evaluate the accuracy of CBCT in comparison with conventional intraoral radiographs used in endodontic procedures. Materials and Methods. Statistical analysis was performed on 101 patients with previous endodontic treatments with the relative radiographic documentation (preoperative, postoperative, and follow-up intraoral X-ray) that had underwent at CBCT screening for surgical reasons. The CBCT scans were evaluated independently by two operators and compared with the corresponding periapical images. Results. Our analysis shows that the two radiological investigations statistically agree in 100% of cases in the group of patients without any endodontic sign. In the group of patients with an endodontic pathology, detected with CBCT, endodontic under extended treatments (30.6%), MB2 canals in nontreated maxillary molars (20.7%), second canals in nontreated mandibular incisors (9%), root fractures (2.7%), and root resorption (2.7%) were not always visible in intraoral X-ray. Otherwise, positivity in the intraoral X-ray was always confirmed in CBCT. A radiolucent area was detected in CBCT exam in 46%, while the intraoral X-ray exam was positive only in 18%. Conclusions. Our study shows that some important radiological signs acquired using CBCT are not always visible in periapical X-ray. Furthermore, CBCT is considered as a II level exam and could be used to solve diagnostic questions, essential to a proper management of the endodontic problems.